Distribution, Identification and Management of Two-Leaf Nightshade (Solanum diphyllum), an Invasive Plant in Florida - Stephen H. Brown; Chris Marble; Stephen F. Enloe (EDIS, 2020)
Two-leaf nightshade, Solanum diphyllum, is a member of the Solanaceae or potato family. It is native to Mexico southwards to Costa Rica. It has escaped cultivation in Florida and grows as far north as Duval County and from Volusia County south to Miami-Dade County. A "bird-dispersed" volunteer, it occurs in urban and conservation areas and on disturbed land. The plants produce abundant berries with many many small seeds. This new 5-page publication of the UF/IFAS Environmental Horticulture Department is primarily intended for Florida gardeners, landscapers, and land managers, and it contains information on identification, flowering, fruiting, and management recommendations for this widely occurring plant. Written by Stephen H. Brown, Chris Marble, and Stephen F. Enloe. https://edis.ifas.ufl.edu/ep588